Necrotizing fasciitis of the abdominal wall caused by Serratia marcescens - Naheed A. Lakhani; Umesh Narsinghani; Ritu Kumar (MDPI AG, 2015)
In this article, we present the first case of necrotizing fasciitis affecting the abdominal wall caused by Serratia marcescens and share results of a focused review of S. marcescens induced necrotizing fasciitis. Our patient underwent aorto-femoral bypass grafting for advanced peripheral vascular disease and presented 3 weeks postoperatively with pain, erythema and discharge from the incision site in the left lower abdominal wall and underwent multiple debridement of the affected area. Pathology of debrided tissue indicated extensive necrosis involving the adipose tissue, fascia and skeletal muscle. Wound cultures were positive for Serratia marcescens. She was successfully treated with antibiotics and multiple surgical debridements. Since necrotizing fasciitis is a medical and surgical emergency, it is critical to examine infectivity trends, clinical characteristics in its causative spectrum. Using PubMed we found 17 published cases of necrotizing fasciitis caused by Serratia marcescens, and then analyzed patterns among those cases. Serratia marcescens is prominent in the community and hospital settings, and information on infection presentations, risk factors, characteristics, treatment, course, and complications as provided through this study can help identify cases earlier and mitigate poor outcomes. Patients with positive blood cultures and those patients where surgical intervention was not provided or delayed had a higher mortality. Surgical intervention is a definite way to establish the diagnosis of necrotizing infection and differentiate it from other entities.